RELATIONSHIP BETWEEN ANXIETY AND STUDENT WILLINGNESS TO PARTICIPATE IN THE COVID-19 VACCINATION AT MTSN 1 WONOGIRI - Wahyuningsih Wahyuningsih; Marni Marni; Novita Nurhidayati; Atik Setiyaningsih (LPPM Universitas Duta Bangsa Surakarta, 2022)
In an effort to overcome the covid-19 pandemic, the covid-19 vaccination aims to reduce the transmission/transmission of covid-19, reduce morbidity and mortality due to covid-19, achieve group immunity in the community (herd immunity) and protect the community from covid-19 so that they remain safe. productive socially and economically. Anxiety, which was one of the problems that occurred during the Covid-19 pandemic, turned out to be a problem also when the Covid-19 vaccine was available.The purpose of the study was to determine the relationship between anxiety and students' willingness to participate in the covid-19 vaccination at MTsN 1 Wonogiri. The results of the research eliminate anxiety in the face of vaccination and publication of scientific journals as a form of the tri dharma of higher education.The analytical descriptive research method with a cross sectional approach was chosen in this study to determine the relationship between anxiety and the willingness of students at MTsN 1 Wonogiri. This study uses a snowball sampling technique considering the condition is still a pandemic, so filling out the questionnaire using a google form with the cooperation of the school.The results of his research from 150 respondents, 131 respondents experienced mild anxiety and 19 respondents experienced moderate anxiety. For data on willingness to be vaccinated, out of 150 respondents, 144 students were willing to be vaccinated and 6 students were not willing to be vaccinated. For bivariate data, out of 131 students who experienced mild anxiety, 4 of them were not willing to be vaccinated because they had never been exposed to information about vaccination. Meanwhile, of the 19 students who experienced moderate anxiety, 2 of them were not willing to vaccinate without a clear reason for not being willing to vaccinate.In conclusion; there is a significant relationship between anxiety and willingness to vaccinate students at MTsN 1 Wonogiri. Suggestions for providing information and socialization about vaccination are very important to be carried out / given to increase the coverage of vaccination targets in the community